Plasmodium vivax in the era of the shrinking P. falciparum map - Price, RN; Commons, RJ; Battle, KE; Thriemer, K; Mendis, K (Cell Press, 2020)
Plasmodium vivax is an important cause of malaria, associated with a significant public health burden. Whilst enhanced malaria-control activities have successfully reduced the incidence of Plasmodium falciparum malaria in many areas, there has been a consistent increase in the proportion of malaria due to P. vivax in regions where both parasites coexist. This article reviews the epidemiology and biology of P. vivax, how the parasite differs from P. falciparum, and the key features that render it more difficult to control and eliminate. Since transmission of the parasite is driven largely by relapses from dormant liver stages, its timely elimination will require widespread access to safe and effective radical cure.